The role of storage protein fractions in slowing starch digestion in chickpea seed. (August 2022) - Tan, Xiaoyan; Li, Changfeng; Bai, Yeming; Gilbert, Robert G.
Abstract: Protein fractions with various digestion properties can have different effects on starch digestibility in chickpea seed. This study investigates these effects by tracking the distributions in digesta of starch, albumin, globulin and glutelin fractions to explain how these proteins play roles throughout the digestion process. The in vitro digestion kinetic analyses were conducted on six chickpea varieties and digesta proteins were separated and quantified. Correlation analysis was performed on the resulting data to identify the relationships between starch digestion and the content of each protein. Cooking changed the solubility of native globulin, with 70–80% of globulins becoming alkali-soluble glutelin-like fraction. During digestion, the glutelin-like and globulin-like fractions were the major insoluble proteins affecting starch hydrolysis, due to their low enzymatic digestibility and the formation of gels. Starch digestibility was negatively correlated with the globulin-like fraction content while showing no direct relationship with that of the glutelin-like fraction. Pasting properties and spatial distributions seen by adding starch to globulin and glutelin indicated that globulin formed a stable paste with starch during heating, thus affecting starch gelatinization, while glutelin was much easier to be separated from starch, although it produced hard and viscous gels. These results could be useful for the development of chickpea foods with desirable properties: for example, higher globulin content is expected to lead to lower starch digestibility. Graphical abstract: Image 1 Highlights: Storage globulin and glutelin are the major proteins inhibiting chickpea starch digestion. Protein complex during digestion is mainly composed of glutelin-like fraction. Globulin reduces starch digestibility by forming stable globulin-starch paste. Glutelin-starch mixture is unstable under heating.